INTERLANGUAGE (ENGLISH-UZBEK, ENGLISH-RUSSIAN) SPECIFICITIES - Axmadjonova Oydinoy; Moydinova Sh (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article explores the phenomenon of interlanguage with specific focus on the interactions  between  English  and  two  commonly  learned  languages  in  Uzbekistan: Uzbek and Russian. It outlines the distinctive linguistic influences, transfer errors, and pedagogical challenges that emerge during second language acquisition. The paper also offers methodological insights for educators teaching English to Uzbek and Russian-speaking learners.